Proceedings of the 12th ACM SIGSOFT Twelfth International Symposium on Foundations of Software Engineering 2004
DOI: 10.1145/1029894.1029930
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of defect projection models for widely-deployed production software systems

Abstract: Defect-occurrence projection is necessary for the development of methods to mitigate the risks of software defect occurrences. In this paper, we examine user-reported software defectoccurrence patterns across twenty-two releases of four widelydeployed, business-critical, production, software systems: a commercial operating system, a commercial middleware system, an open source operating system (OpenBSD), and an open source middleware system (Tomcat). We evaluate the suitability of common defect-occurrence mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…Dynamic defects models follow distribution patterns including Rayleigh distribution and other similar curves [40,41,42]. Ref.…”
Section: Related Workmentioning
confidence: 99%
“…Dynamic defects models follow distribution patterns including Rayleigh distribution and other similar curves [40,41,42]. Ref.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [26] have shown that in the context of post-release defects the naïve models like moving average are not sufficient, but Weibull and Rayleigh models render more accurate results. In the light of this we recommend to use the results of Li et al when predicting post-release defect inflow and our results/forecasting model when working with pre-release defects.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, the effective methods of dynamic testing management for new distributed development paradigm as typified by the open source project have been only a few presented [3], [4], [5], [6]. Also, there are some interesting research papers in terms of the cloud hardware, cloud service, and cloud performance evaluation [7], [8].…”
Section: Introductionmentioning
confidence: 99%